Monocyte/macrophage‐derived soluble CD163: a novel biomarker in multiple myeloma. (20th March 2014) - Andersen, Morten N.; Abildgaard, Niels; Maniecki, Maciej B.; Møller, Holger J.; Andersen, Niels F.
Abstract Objectives Macrophages play an important role in cancer by suppression of adaptive immunity and promotion of angiogenesis and metastasis. Tumor‐associated macrophages strongly express the hemoglobin scavenger receptor CD163, which can also be found as a soluble protein in serum and other body fluids (soluble CD163, sCD163). In this study, we examined serum sCD163 as a biomarker in patients with newly diagnosed multiple myeloma. Methods Peripheral blood (n = 104) and bone marrow (n = 17) levels of sCD163 were measured using an enzyme‐linked immunosorbent assay. Results At diagnosis, high sCD163 was associated with higher stage according to the International Staging System (ISS) and with other known prognostic factors in multiple myeloma (creatinine, C‐reactive protein, and beta‐2 microglobulin). Soluble CD163 decreased upon high‐dose treatment, and in a multivariate survival analysis including the covariates treatment modality and age at diagnosis, higher levels of sCD163 were associated with poor outcome (HR = 1.82; P = 0.010). The prognostic significance of sCD163 was lost when including ISS stage in the model (HR = 1.51; P = 0.085). Soluble CD163 values were significantly higher in bone marrow samples than in the matched blood samples, which indicate a localized production of sCD163 within the bone marrow microenvironment. Conclusions Soluble CD163 was found to be a prognostic marker in patients with multiple myeloma. This may indicate that macrophages and/or monocytes have an important role in the bone marrow microenvironment of myeloma patients, supporting myeloma cell proliferation and survival. We propose the serum sCD163 value 1.8 mg/L as a cutoff concentration for survival analysis in patients with multiple myeloma, which should be validated in future studies.